Assessment of use pattern, needs,preferences and overall satisfaction to determine the quality aspect of a neighbourhood park - Abdul Malek, Nurhayati (2011)
The purpose of this study was to gain an increased understanding on the quality aspects of neighbourhood green open spaces among Malaysian park users’. Hence, this research explores the causal relationship between, Quality green open spaces (QGOS), Use patterns (U), Needs (ND), Preferences (PR) and Overall satisfaction (OS) towards achieving a Quality Neighbourhood Park Criteria (QNPC). A survey was administered to a sample of Malaysian neighbourhood park users’. A total of 414 daily neighbourhood park user responded to the survey. Structural equation modeling (SEM) technique was used to examine the hypothesized model of causal relationships among quality green open spaces variables, use of outdoor venues, preferences towards outdoor activities, needs in outdoor recreation as well as the overall satisfaction towards the neighbourhood green open spaces using the AMOS 18 program. This study addresses the question of why does quality in green open spaces or Neighbourhood Parks is needed? What are the evaluation criteria to determine the quality aspect of Neighbourhood Parks?. The research argues that by integrating construct of quality green open spaces, use, preference, needs and satisfaction will help to develop the quality aspect for neighbourhood parks. The results of this study support a direct relationship between QGOS variables (operative, ambience, landscape elements, facilities, accessibility and recreational elements) and OS variables (satisfaction and dissatisfaction) towards the neighbourhood green open spaces. This study also found a positive relationship between QGOS with U (passive and active usage & spaces utilized) and OS with U. This study suggested that PR on Neighbourhood Park had significant direct effects on QGOS as well as OS on PR (recreational preferences, design preferences, amenity preferences and personal preferences). These results provide an important contribution in the sense that QGOS variable may have various causal effects on the individual’s OS, U, PR and ND through subjective perception of outdoor recreation in a Neighbourhood Parks.